Contrasting portuguese and international service quality management in the Algarve hotel industry - Cândido, Carlos (2014)
This paper establishes a contrast between the management of three different kinds of hotels operating in the Algarve: international chain hotels, portuguese chain hotels and independent hotels. The dimensions along which the contrast is established are fourteen service quality gaps (SQGs), taken from a model which has been developed in a previous paper by the author and a co-author (Cândido et al., 2000). Sample data has been collected through a questionnaire implemented in the population of four and five star hotels of the Algarve (FFSHA). Data analysis involves descriptive statistics and some statistical tests. In general, descriptives emphasise differences between the hotel groups and raise concerns about possible inconsistent management practices. The paper concludes with several specific suggestions to improve service quality in the FFSHA.